Ammonia-modified graphene sheets decorated with magnetic Fe3O4 nanoparticles for the photocatalytic and photo-Fenton degradation of phenolic compounds under sunlight irradiation - Boruah, Purna K.; Sharma, Bhagyasmeeta; Karbhal, Indrapal; Shelke, Manjusha V.; Das, Manash R. (Journal of hazardous materials, 2017)
Synthesis of easily separable and eco-friendly efficient catalyst with both photocatalytic and photo-Fenton degradation properties is of great importance for environment remediation application. Herein, ammonia-modified graphene (AG) sheets decorated with Fe3O4 nanoparticles (AG/Fe3O4) as a magnetically recoverable photocatalyst by a simple in situ solution chemistry approach. First, we have functionalized graphene oxide (GO) sheets by amide functional group and then Fe3O4 nanoparticles (NPs) are doped onto the functionalized GO surface. The AG/Fe3O4 nanocomposite showed efficient photocatalytic activity towards degradation of phenol (92.43%), 2-nitrophenol (2-NP) (98%) and 2-chlorophenol (2-CP) (97.15%) within 70–120 min. Consequently, in case of photo-Fenton degradation phenomenon, 93.56% phenol, 98.76% 2-NP and 98.06% of 2-CP degradation were achieved within 50–80 min using AG/Fe3O4 nanocomposite under sunlight irradiation. The synergistic effect between amide functionalized graphene and Fe3O4 nanoparticles (NPs) enhances the photocatalytic activity by preventing the recombination rate of electron-hole-pair in Fe3O4 NPs. Furthermore, the remarkable reusability of the AG/Fe3O4 nanocomposite was observed up to ten cycles during the photocatalytic degradation of these phenolic compounds.